(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: Identify experiences of the person with intestinal ostomy related to their social life. Methods: Descriptive study, qualitative in nature, carried out with ten people with intestinal ostomy. Data collection was performed at the Stomatherapy Service of a teaching hospital in the Federal District, through semi-structured interviews relating to family and social experience before and after the ostomy. Results: Six men and four women participated, with a mean age of 49 years, most with a permanent colostomy. From the analysis, two categories emerged: “What is it like to live with an ostomy and its challenges”; and “Strategies developed in the face of changes”. In the first category, the following stand out: self-care, lack of adequate bathroom, work activity, eating habits, disruption of body image and embarrassing situations. In the second category, they seek to support religiosity, maintain positive feelings and preserve emotional balance. Conclusion: The ostomy interferes with family and social life. It was evident that the person with ostomy develops strategies to face changes. It is believed that social isolation stems, in part, from the lack of information from society, the lack of quality material that offers comfort and safety, and, finally, the lack of adapted public and private bathrooms.